Neglect of Children Perspective of Law no. 35 of 2014 and Law No. 17 of 2016 - Slamet Sudarsono; Priambodo Adi Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The purpose of this research is to determine the sanctions against perpetrators of child neglect according to Islamic law and Law Number 17 of 2016 concerning Child Protection. The research method for normative juridical research is by examining or analyzing secondary data in the form of secondary legal materials by understanding law as a set of regulations or positive norms in the legal system that regulates the problems in this research. The results of sanctions against perpetrators of child neglect according to law number 35 of 2014 concerning protection are in Law Number 17 of 2016 concerning Child Protection which is regulated in article 76B with sanctions in article 77B.